Strategies for preventing fire in high-rise residential buildings / Andrea Valerie Law - Andrea, Valerie Law (2018)
In this study, high-rise residential building is at high risk of fire and currently there are no comprehensive standards for fire prevention. High-rise residential buildings focus many challenges to prevent fires in term of fire protection facilities by building management, resident’s involvement with building fire safety and the importance of fire prevention among residents. Therefore, the focus of this study is to develop strategies for fire prevention in high-rise residential buildings. There are two proposed strategies and checklist developed for building management and residents. Methods such as survey and benchmark are used in this study. The survey is distributed to expert’s and as results, the opinion is used to priorities fire prevention implementation. Whereas, benchmark is used to develop strategies and guideline to manage fire protection system in the building. Then, a checklist is developed to ensure the strategies are practical and indirectly enhance fire prevention practices. The success of strategies and checklist implementation will able to give positive changes toward fire prevention in high-rise buildings. Since this strategy is developed based on expert’s opinion and benchmark from other countries, in the future the study can be improve by high-rise residents and building management involvement to practice the strategies and response feedback for better implementation. Keywords: Fire prevention, high-rise residential, expert's opinion, benchmark, proposed strategies, checklist.